Variasi Musiman Hubungan Antara Parameter Oceanografi Dengan Hasil Tangkapan Ikan Tongkol Berdasarkan Data Harian Di Selat Bali - Sastra, I Gusti Agung Bagus Wisesa; Karang, I Wayan Gede Astawa; As-syakur, Abd. Rahman; Suteja, Yulianto (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018)DO - 10.24843/jmas.2018.v4.i01.109-119, 2017)
Mackerel fish that classified pelagic fish and an export commodity in Indonesia. Distribution of mackerel fish are foundn all Indonesian waters, one of them in the Bali Strait. Distribution of mackerel fish influenced by oceanographic condition such as sea surface temperature (SST) and chlorophyll-a concentration. SST and chlorophyll-a concentrations are environmental parameters that can provide information on fishing ground. The purpose of this research is explained the temporal fluctuation and relationship between SST and chlorophyll-a concentration with mackerel fish had been catch in Bali Strait waters during 2011-2016. Data were analyzed using simple correlation analysis with 95% confidence interval. Temporally, the highest average SST occurred during the transition season I (March-May) and the lowest in the east season (June-August). The highest average chlorophyll-a concentration occurs in the east season and the lowest in the west season (December-February). The highest catch of mackerel fish occurred during transitional season II (September-November) and lowest in west season. The association between SST and chlorophyll-a concentration on mackerel fish catch showed low correlation with significant relationship, whereas concentration between SST and chlorophyll-a concentration strong with significant correlation